On the harmonic evolute of quasi normal surfaces - Körpınar, Talat; Kaymanlı, Gül Uğur (Editura Bibliotheca-Bibliotheca Publ House, 2020)
In this paper, we study a harmonic evolute surface of quasi normal surface associated with quasi frame. We construct quasi normal surface with first and second fundamental forms. Moreover, we determine harmonic evolute surface of quasi normal surface by using these fundamental forms. Finally, we obtain some new results about these new surfaces.
Keywords: Bonnet Surfaces; Curvatures; Fundamental Forms; Normal Spherical Image